Praca czy rodzina? Aktywność zawodowa młodych kobiet na etapie wchodzenia w dorosłość = Work or family? Professional activity of young women as they enter adulthood - Grotowska-Leder, Jolanta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article discusses the professional and family choices of young women entering adulthood in the context of the dynamically changing labour market in Poland at the turn of the century and modernization of family life patterns. The analysis is based on the concepts of transition from youth to adulthood, labour market changes in post-modern society and work-lifebalance. The empirical ?ndings are based on the qualitative results obtained in the NCN project "Public Policies for Full Adulthood in Poland". The conclusions on the di?erentiation of choices between professional and family roles are exempli?ed by four quasi biographical interviews with thirty-yearold female residents of Łódź and one of the districts of Łódź Province.
Keywords: tranzycja w dorosłość; młode kobiety; rola zawodowa; rodzina; transition into adulthood; young women; professional role; family